Structural, electrical, optical and dielectric properties of yttrium substituted cadmium ferrites prepared by Co-Precipitation method. Issue 13 (September 2020) - Amin, Nasir; Ul Hasan, Muhammad Sajjad; Majeed, Zahid; Latif, Zartashia; Ajaz un Nabi, Muhammad; Mahmood, Khalid; Ali, Adnan; Mehmood, Kiran; Fatima, Muneeba; Akhtar, Maria; Arshad, Muhammad Imran; Bibi, Aisha; et al.
Abstract: The yttrium substituted cadmium ferrites having composition Cd1-x Yx Fe2 O4 (X = 0.00, 0.125, 0.250, 0.375, 0.500) were synthesized by the co-precipitation method and sintered at 1100 °C for 6 h. Structural, morphological, electrical, optical and dielectric characteristics were explored by XRD, SEM, EDS, FTIR, I–V two probes, UV–Vis and LCR techniques.XRD results confirmed the cubic structure of spinel ferrites. A decrease in lattice constants of the prepared samples was observed with the substitution of Y ions and was attributed to the difference in ionic radii of Y 3+ (0.95 Å) and Cd 2+ (0.97 Å) ions. Cationic distributions, ionic radii of both tetrahedral and octahedral sites, tolerance factor, oxygen positional parameters, bond lengths, interatomic distances, positional parameters and bond length angles were calculated from XRD data. The morphology of the prepared ferrites was studied using SEM and results ratified the XRD results. EDS confirmed the presence of all inserted elements in Cd1-x Yx Fe2 O4 composition. DC resistivity and drift mobility of soft-ferrites were found to be increased from 1.047 × 10 8 –4.822 × 10 10  Ω-cm and 5.87 × 10 −12 – 1.045 × 10 −14 cm 2 V −1 s −1, respectively, at 523 K with yttrium content confirming the behavior of semiconductor materials. The optical band gap energy calculated from the UV–Vis pattern of the Cd1-x Yx Fe2 O4 system was decreased from 3.6011 to 2.8153 eV. DC resistivity and optical band gaps exposed inverse relation. FTIR results revealed lower and upper-frequency absorption bands in the ranges of 419.31–417.01 cm −1 and 540.95–565.70 cm −1, respectively. Dielectric constant and dielectric losses were in decreasing order, while ac conductivity revealed rising behavior with increasing frequency. Results showed the potential of yttrium doped Cd nanoferrites for applications in high-frequency microwave absorbing devices.